A rare case report of complete transposition of the femoral artery and vein - Hassani, Mohammad; Rabbani, Amirhassan; Pishgahi, Mohammad; Bakhshaei Shahrbabaki, Peyman (Researcher Bulletin of Medical Sciences, 2021)
In the inguinal region at normal anatomical situation the artery is positioned lateral to vein and by this figure artery and vein get out under inguinal ligament and entrance to this region. Every surgeon (general surgeon, vascular surgeon or orthopaedic) that works at this region should know anatomical anomaly and variation of these vessels in inguinal region. Dissection at this region without knowing these variations could damage the vessels especially femoral artery. Some times this variations could induce compression on the vein and induce deep vein thrombosis. In this case while exploring femoral artery for transfemoral thrombectomy, femoral vein was found in the arteries anatomical position and complete transposition of artery and vein was founded. In conclusion, knowing normal variations and anomalies while dissecting this area helps us for lowering iatrogenic vascular trauma and complications.